Significance in Language A Theory of Semantics - Feist, Jim (Routledge Studies in Linguistics, 2022)
This book offers a unique perspective on meaning in language, broadening the scope of existing understanding of meaning by introducing a comprehensive and cohesive account of meaning that draws on a wide range of linguistic approaches. The volume seeks to build up a complete picture of what meaning is, different types of meaning, and different ways of structuring the same meaning across myriad forms and varieties of language across such domains, such as everyday speech, advertising, humour, and academic writing. Supported by data from psycholinguistic and neurolinguistic research, the book combines different approaches from scholarship in semantics, including formalist, structuralist, cognitive, functionalist, and semiotics to demonstrate the ways in which meaning is expressed in words but also in word order and intonation. The book argues for a revised conceptualisation of meaning toward presenting a new perspective on semantics and its wider study in language and linguistic research. This book will appeal to scholars interested in meaning in language in such fields as linguistics, semantics, and semiotics.